Exploring the boundaries and ontology of Psychiatric Disorders (PDs) using the Homeostatic Property Cluster (HPC) model: A previous version of this paper has been mistakenly published on April 19, 2021. Please refer to the current revised version. - Casali, Marco (Lato Sensu: Revue de la Société de philosophie des sciences, 2021)
In this article we show that, even though the classification and diagnosis of Psychiatric Disorders (PDs) are performed according to essentialist terms, the psychiatric diagnoses currently employed, (i.e., clinical psychiatry) do not actually meet these criteria. Diagnosis is performed operationally. In this paper, we suggest a change of perspective. We reject essentialism relating to PDs and argue for the Homeostatic Property Cluster (HPC) model, which allows a greater insight into the ontology of PDs than the operational perspective. More specifically, we argue that the HPC model allows for a synthesis of continuous and discrete methods of understanding the boundaries between PDs. Finally, we specify in a more general manner, the kind of ontology we deal with when adopting the HPC model, arguing that this model can be viewed as a mirror device, reflecting the ontological features of PDs.